Ocular molluscum contagiosum - A case report (KYAMC Journal, 2017)
Molluscum contagiosum is a viral disease of the skin caused by poxvirus. Infection is usually spread by direct contact, particularly among children and young adults. It may occur on the skin and mucous membranes, with a predilection for the trunk and anogenital areas. Ocular molluscum contagiosum is very rare. Here we present a case of right lower eyelid region molluscum contagiosum. This patient is a 28 years old young woman from Ramchandropur, Pabna, Bangladesh. She noticed a painless swelling in her right lower eyelid for six months. Examination revealed a firm, rough and non-tender growth. There was no visual disturbance. After excisional biopsy, histopathological examination was performed. Microscopically, it shows verrucous epidermal hyperplasia and multiple intracytoplasmic molluscum bodies which are diagnostic key feature of molluscum contagiosum.KYAMC Journal Vol. 5, No.-2, Jan 2015, Page 537-539